CONTENT - Selangga, Dewa Gede Wiryangga (International Journal of Biosciences and Biotechnology, 2020)
CONTENT FO R EWORD .................................................................................................................... iv   TOXICITY TEST OF Gracilaria sp. AGAINS T Aspergillus niger van Tieghem AND THE PHYTOCHEMICAL ANALYSIS Nevy Widya Pangestika, I Gede Putu Wirawan, and I Ketut Suada.................................... 1   RUNNER-TIP CULTURE OF STRAWBERRY ( Fragaria x ananassa Duch) GROWN ON SEVERAL SHOOT-INDUCTION MEDIUM Rindang Dwiyani, Hestin Yuswanti, Ni Nyoman Ari Mayadewi, and Yuyun Fitriani......... 10   Citrus TISSUE CULTURE WITH TWO DIFFERENT APPROACHES Firoozeh Chamandoosti......................................................................................................... 19   PHYTOCHEMICAL ANALYSIS AND ANTIOXIDANT ACTIVITY OF PURNAJIWA FRUIT EXTRACT (Euchresta horsfieldii (Lesch.) Benn.) Romulia Trielva Apriliani, I Gede Putu Wirawan, and Wayan Adiartayasa .................................................................................................................................................. 31   IDENTIFICATION OF AGARWOOD SAPWOOD CHEMICAL COMPONENTS FROM FUNGAL INOCULATION RESULTS ON Gyrinops versteegii (Gilg.) DOMKE PLANTS I M. Mega and N.L. Kartini..................................................................................................... 40   G U I D E FOR AUTHORS